Extinction rate of discovered and undiscovered plants in Singapore. Issue 5 (23rd June 2020) - Kristensen, Nadiah P.; Seah, Wei Wei; Chong, Kwek Yan; Yeoh, Yi Shuen; Fung, Tak; Berman, Laura M.; Tan, Hui Zhen; Chisholm, Ryan A.
Abstract: Extinction is a key issue in the assessment of global biodiversity. However, many extinction rate measures do not account for species that went extinct before they could be discovered. The highly developed island city–state of Singapore has one of the best‐documented tropical floras in the world. This allowed us to estimate the total rate of floristic extinctions in Singapore since 1822 after accounting for sampling effort and crypto extinctions by collating herbaria records. Our database comprised 34, 224 specimens from 2076 native species, of which 464 species (22%) were considered nationally extinct. We assumed that undiscovered species had the same annual per‐species extinction rates as discovered species and that no undiscovered species remained extant. With classical and Bayesian algorithms, we estimated that 304 (95% confidence interval, 213–414) and 412 (95% credible interval, 313–534) additional species went extinct before they could be discovered, respectively; corresponding total extinction rate estimates were 32% and 35% (range 30–38%). We detected violations of our 2 assumptions that could cause our extinction estimates, particularly the absolute numbers, to be biased downward. Thus, our estimates should be treated as lower bounds. Our results illustrate the possible magnitudes of plant extirpations that can be expected in the tropics as development continues. Abstract : Article impact statement : The number of species that went extinct before they could be discovered can be estimated from museum records. Abstract : Tasa de Extinción de Plantas Descubiertas y No Descubiertas en Singapur Resumen: La extinción es un tema importante para la valoración de la biodiversidad global. Sin embargo, muchas medidas de la tasa de extinción no consideran a las especies que se extinguieron antes de que pudieran ser descubiertas. Singapur, la ciudad‐estado isleña altamente desarrollada, tiene una de las floras mejor documentadas del mundo. Esto nos permitió estimar la tasa total de las extinciones florísticas en Singapur desde 1822 después de considerar el esfuerzo de muestreo y las criptoextinciones cuando recopilamos los registros de herbarios. Nuestra base de datos incluyó 34, 224 especímenes de unas 2, 076 especies nativas, de las cuales 464 especies (22%) estaban consideradas como extintas a nivel nacional. Asumimos que las especies no descubiertas tuvieron la misma tasa anual de extinción por especie que las especies descubiertas y que ninguna especie no descubierta permanecía en existencia. Con algoritmos clásicos y bayesianos, respectivamente, estimamos que 304 (95% IC 213–414) y 412 (95% IC 313–534) especies adicionales se extinguieron antes de que fueran descubiertas; las estimaciones correspondientes de la tasa de extinción total fueron 32% y 35% (rango de 30–38%). Detectamos violaciones en nuestras dos suposiciones que podrían causar que nuestras estimaciones de extinción, particularmente los números absolutos, tuvieran un sesgo hacia abajo. Por lo tanto, nuestras estimaciones deberían ser tratadas como límites inferiores. Nuestros resultados ilustran las magnitudes posibles de las extirpaciones de plantas que pueden esperarse en los trópicos conforme el desarrollo continúa. 摘要: 物种灭绝是全球生物多样性评估的一个关键问题。然而, 许多灭绝率估计中并没有考虑到那些在被发现之前就已经灭绝的物种。高度发达的岛国新加坡拥有世界上记载最完整的热带植物群, 这使得我们能够通过整理草本植物记录来统计采样工作量和隐秘的灭绝事件, 以估计新加坡自1822 年以来植物灭绝的总速率。本研究的数据库包括来自 2076 个本地物种的 34, 224 个标本, 其中有 464 个物种 (22%) 被认为在全国范围内灭绝。我们假设未被发现的物种年均灭绝率与已发现物种相同, 且已没有未被发现的现存物种。利用经典算法和贝叶斯算法, 我们分别估计出 304 个 (95% 置信区间为 213 ‐ 414) 和 412 个 (95% 可信区间为 313 ‐ 534) 新物种在被发现之前就已经灭绝; 相应的总灭绝率估计分别为 32% 和 35% (范围为 30 ‐ 38%) 。我们还发现存在违反上述两个假设的情况, 这可能导致我们对灭绝情况的估计值偏低, 特别是对绝对数值的估计。因此, 我们对灭绝情况的估计值应被视为下限。本研究表明, 随着热带地区的发展, 植物灭绝的规模可能会不断扩大。【翻译:胡怡思;审校:聂永刚】